2022
DOI: 10.1186/s12877-022-03518-1
|View full text |Cite
|
Sign up to set email alerts
|

Latent profile analysis for quality of life in older patients

Abstract: Background Quality of life (QOL) is a complex concept known for being influenced by socio-demographic characteristics, individual needs, perceptions and expectations. The study investigates influences of such heterogeneous variables and aims to identify and describe subgroups of older patients who share similar response patterns for the four domains (physical health, psychological health, social relationships and environment) of World Health Organization Quality of Life instrument, Short Form (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…To our knowledge, this is the first study on the latent profile analysis of health literacy in patients with gout. Latent profile analysis, unlike the variable-centered approach, allows for differential grouping of individuals and facilitates further targeting of interventions to different subgroups of patients, especially for disadvantaged patients [ 27 , 28 ]. Our study identified heterogeneity in the health literacy of patients with gout, who can be categorized into three subgroups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first study on the latent profile analysis of health literacy in patients with gout. Latent profile analysis, unlike the variable-centered approach, allows for differential grouping of individuals and facilitates further targeting of interventions to different subgroups of patients, especially for disadvantaged patients [ 27 , 28 ]. Our study identified heterogeneity in the health literacy of patients with gout, who can be categorized into three subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous research has shown that health literacy is complex and perhaps heterogeneous [ 25 ], and the variable-centered approach does not take into account individual heterogeneity, suggesting a person-centered approach [ 26 ] is warranted. Latent profile analysis is a person-centered approach that groups individuals homogeneously based on differences in their scores on each variable (dimensions of health literacy), which is conducive to studying the characteristics of different types of populations [ 26 , 27 ]. This approach categorizes individuals into different groups to help target interventions to different subgroups, which can lead to better intervention outcomes, especially for disadvantaged patients [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified distinct QOL profiles in different populations. For instance, one Romanian study identified three QOL subgroups using the World Health Organization Quality of Life-Brief (WHOQOL-BREF) among the patients 65 years of age and older from Bucharest on the geriatric ward ( 26 ). Another similar study ( 27 ) used the Stoma Quality of Life Scale (SQOL) to identify four profiles for patients with a stoma.…”
Section: Introductionmentioning
confidence: 99%
“…Latent profile analysis (LPA) is an individual-centered analysis technique that can better distinguish group categories by grouping individuals with similar response patterns into the same subgroup and elucidating response characteristics and the proportion of individuals on different entries or dimensions [ 22 ]. Latent profile analysis has been widely utilized in numerous studies and is regarded as having strong scientific and persuasive power in identifying subgroup classification [ 23 , 24 ], and [ 25 ]. This study aims to investigate the potential categories of nursing students' perceptions of decent work and the differences in their characteristics using the latent profile analysis approach with the goal of providing a reference for career guidance in universities and related departments.…”
Section: Introductionmentioning
confidence: 99%